The Role of Transformational Leadership in Improving the Performance of the Yellow Troops: A Case Study in Jombang Regency - Eko Cahyono; Moh. Ja’far Sodiq Maksum (Management and Education Journal, 2025)
This study aims to analyze the role of transformational leadership in improving the performance of pasukan kuning (municipal sanitation workers) in Jombang Regency. As the frontline of urban cleanliness, pasukan kuning face challenges such as heavy workloads, limited educational backgrounds, and low social recognition. Using a descriptive qualitative approach, data was collected through in-depth interviews with officials of the Environmental Agency, field supervisors, and sanitation workers, as well as direct field observations. The findings indicate that transformational leadership is reflected in providing motivation, moral examples, individualized consideration, and work empowerment. These practices result in improved discipline, enhanced intrinsic motivation, small-scale innovations in work methods, and stronger team synergy. However, limitations remain, particularly regarding structural support and institutionalized incentives. The study contributes theoretically to the discourse on public sector human resource management and offers practical recommendations for strengthening training, reward systems, and welfare policies for sanitation workers in Jombang.